Calculation of residual strength of shot casing - Chang, Lyu (International Journal of Scientific Research and Management (IJSRM), 2024)
There is a significant spanning difference in scale between the shot-hole borehole and the oil well casing, and the stress singularity at the shot-hole usually occurs in conventional finite element simulations, which cannot be avoided even when elastic-plasticity is brought into the calculation, leading to errors in the simulation results. In addition, a large amount of mesh refinement is required near the shot holes, which also increases the computational volume. In order to solve this problem, this paper adopts the RVE technique, which establishes the RVE model in and around the original shot hole location, and then establishes the casing model after RVE treatment to avoid the occurrence of stress singularity. After RVE treatment, additional mesh refinement is no longer required near the shot hole, which reduces the amount of calculation to a certain extent. The feasibility of the RVE-treated casing in simulation calculations was verified by performing elasto-plastic static finite element simulations of the conventional shot hole casing and the RVE-treated casing in ANSYS finite element simulation software. The results show that the RVE-treated model optimizes the simulation effect in the original shot hole region. The RVE-treated casing model is used to calculate the residual strength coefficients under different shot hole parameters, and the fitting analysis is carried out. The results show that the residual strength of the casing gradually decreases with the increase of the injection hole diameter under the condition of constant casing parameters, and the residual strength of the casing also gradually decreases with the increase of the number of holes. These findings provide an important reference for the design of oil and gas well production programs.